Development of a Highly Selective, Sensitive, and Fast Response Upconversion Luminescent Platform for Hydrogen Sulfide Detection. (30th November 2015) - Peng, Juanjuan; Teoh, Chai Lean; Zeng, Xiao; Samanta, Animesh; Wang, Lu; Xu, Wang; Su, Dongdong; Yuan, Lin; Liu, Xiaogang; Chang, Young‐Tae
Abstract : Hydrogen sulfide (H2 S) has been recognized as one of most important gaseous signaling molecules mediated by a variety of physiological and pathological processes. Yet, its functions remain largely elusive due to the lack of potent monitoring methods. Hereby this issue is addressed with a powerful new platform—dye‐assembled upconversion nanoparticles (UCNPs). A series of chromophores with different absorption bands and fast responses towards H2 S is combined with UCNPs and results in a library of H2 S sensors with responsive emission signals ranging from the visible to the near‐infrared (NIR) region. These nanoprobes demonstrate highly selective and rapid responses to H2 S in vitro and in cells. Furthermore, H2 S levels in blood can be detected using the developed nanoprobes. Hence the reported H2 S sensing platform can serve as a powerful diagnostic tool to research H2 S functions and to investigate H2 S‐related diseases. Abstract : The request of powerful sensor probes for environmental and bioimaging fields has attracted intensive and enthusiastic research during the past decades. Hereby a new dye‐assembled H2 S sensing platform—dye‐assembled upconversion nanoparticles (UCNPs)—is designed. These probes with emission spectra ranging from visible to near‐infrared (NIR) are applicable for H2 S detection in cells and mice serum.